The impact of brand image and authenticity on Padang City users of Gojek's brand love and loyalty - Agus Harianto; Yasri Yasri (Universitas Negeri Padang, 2023)
This study is to analyze the effect of brand authenticity and brand image on brand love and brand loyalty of Gojek users in the city of Padang. The research method used is descriptive quantitative analysis with SmartPLS 3.0 as an analytical tool. With Purposive Sampling as a sampling technique and 250 samples for Gojek users in the city of Padang in 2022. The research is: (1) There is a significant influence between Brand authenticity and Brand Love. (2) There is a significant influence between Brand love and brand loyalty. (3) There is a significant influence between Brand image and brand love, and (4) There is a significant influence between Brand image and brand loyalty. (5) There is a significant effect of Brand Authenticity on Brand Loyalty in mediating Brand Love. (6)There is a significant effect of Brand Image on Brand Loyalty in mediating Brand Love